Brain and Cognition for Addiction Medicine: From Prevention to Recovery Neural Substrates for Treatment of Psychostimulant-Induced Cognitive Deficits - D’Souza, Manoranjan S. (Frontiers in Psychiatry, 2019)
Addiction to psychostimulants like cocaine, methamphetamine and nicotine poses a continuing medical and social challenge both in the United States and all over the world. Despite a desire to quit drug use, return to drug use after a period of abstinence is a common problem amongst individuals dependent on psychostimulants. Recovery for psychostimulant drug dependent individuals is particularly challenging because psychostimulant drugs induce significant changes in brain regions associated with cognitive functions leading to cognitive deficits. These cognitive deficits include impairments in learning/memory, poor decision making and impaired control of behavioral output. Importantly, these drug-induced cognitive deficits often impact adherence to addiction treatment programs and predispose abstinent addicts to drug use relapse. Additionally, these cognitive deficits can impact effective social and professional rehabilitation of abstinent addicts. The goal of this paper is to review neural substrates based on animal studies that can be pharmacologically targeted to reverse psychostimulant-induced cognitive deficits such as impulsivity and impairment in learning and memory. Further, the review will discuss neural substrates that can be used to facilitate extinction learning and thus reduce emotional and behavioral responses to drug-associated cues. Moreover, the review will discuss some non-pharmacological approaches that can be used either alone or in combination with pharmacological compounds to treat the above mentioned cognitive deficits. Psychostimulant addiction treatment, which includes treatment for cognitive deficits will help promote abstinence and allow for better rehabilitation and integration of abstinent individuals into society.